Deciphering genetic relationships within and among banana (Musa spp.) genome groups using ISSR and SRAP markers - Roshida Soraisham; Punshi Tongbram; Surendrakumar Singh Thingnam; Boris Aheibam; John Zothanzama; Dinamani Singh Lourembam; Robert Thangjam (Journal of Genetic Engineering and Biotechnology)
Characterization and identification of banana into their correct genome groups has been a problematic issue based on morphological and unappropriated molecular markers. In the present study, the genetic relationship between and among 28 banana (Musa spp.) accessions representing 5 genome groups (AAA, BB, AAB, ABB and AB) were evaluated using sequence-related amplified polymorphism (SRAP) and inter simple sequence repeat (ISSR) markers. Although similar genetic relationship parameters were observed with the two markers, the higher values were generated with SRAP profiles as indicated with mean gene diversity value of 0.69 with SRAP and 0.64 with ISSR, polymorphic information content (PIC) of 0.64 with SRAP and 0.59 with ISSR, total genetic diversity (Ht) of 0.39 with SRAP and 0.34 with ISSR, gene diversity within population (Hs) of 0.19 with SRAP and 0.12 with ISSR, coefficient of gene differentiation (Gst) value of 0.51 with SRAP and 0.62 with ISSR and gene flow (Nm)value of 0.51 with SRAP and 0.31 with ISSR. The resulting dendrogram and the population structure also supports and showed the concurrence with the genetic relationship parameters based on the genome groups of the accessions studied. The present finding, also indicates the higher efficacy of SRAP markers over the ISSR markers in the discrimination of banana accessions based on their genome groups by grouping the banana accessions belonging to the different genome groups and ploidy levels. The present finding could be utilized for effective discrimination of banana accessions belonging to different genome groups.